RELATIONSHIP AMONG PERFECTIONISM, RUMINATION AND IMPOSTORISM INEMPLOYEES OF MULTINATIONAL COMPANIES - Jain, Paridhi; Singh, Dr. Suyesha (The journal of contemporary issues in business and government, 2022)
Employees working in multinational companies spend a major chunk of their daily time in the workplace. The competition and threat of survival is growing rapidly. Employees in organizations are under the constant pressure to achieve higher goals to prove themselves. The aspirations of employees are skyrocketing, and they are striving to survive and thrive in a super competitive work environment. The glamourous hustle culture has swept the young workforce off its feet. It has been observed thatorganizations prefer people who tend to have high work drive, extreme work involvement and who can work beyond the capacity. Employees strive for perfection in all domains and an overdrive for perfectionism may lead to maladaptive rumination and impostorism. Impostor phenomenon can affect an individual’s work and family life. Impostorism, perfectionism and rumination are some prominent problems faced by employees working in corporate environments. The presentstudy assesses the relationship among impostorism, perfectionism and rumination in employees working in multinational companies. The sample comprised of 103 individuals (both males and females) working in multinational companies. ‘FFOCI- Short Form’ (Samuel et ah,2014) and ‘Glance Impostor Syndrome Scale’ (Clance, 1985) were used for gathering data.Pearson correlation and multiple regression analysis were computedto assess the association among perfectionism, rumination &impostorism. Findings suggest that perfectionism, rumination and impostorismare positively correlated with each other& perfectionism and rumination significantly predict impostorism in employees working in MNC’s.The findings of the research will help in understanding the dynamics between the selected variables which will further help in formulation of strategies for reducing impostorism, maladaptive perfectionism and rumination and enhancing mental health of working population.